The Impact and Value of Research in the Arts and Humanities - A Systematic Literature Review - Bloch, Carter Walter; Irwin, Alan; Schmidt, Evanthia Kalpazidou; Pedersen, Anna Vigsø; Svendsen , Amalie Due (CFA Scientific Reports, 2025)
Research and research policy have increasingly directed attention towards issues concerning the impact of research. This focus appears to be driven by a range of factors, including: the wish to demonstrate accountability with regard to public funding, the need to measure and benchmark research quality, and a growing interest in understanding and documenting the connection between research and its societal use (Penfield et al., 2014). Research in the Arts and Humanities (A&H) is no exception from this trend, stimulating considerable debate over the impact of A&H research, as well as on how this impact can be demonstrated (Pedersen et al., 2020; Reale et al., 2018). At the same time, there is a lack of consensus on how valuation and impact in A&H can be understood and measured. Indeed, some scholars question whether the ‘impact’ concept is even appropriate in terms of capturing how A&H research matters for society (Belfiore, 2015; Collini, 2012). In contrast to disciplines within Science, Technology, Engineering and Mathematics (STEM), the societal impact of A&H research may be more difficult to grasp. Hence, a better understanding of the nature of A&H research, as well as how value creation takes place, are central to an appreciation of research impact in A&H and the factors that can promote or hinder it. The Danish Centre for Studies in Research and Research Policy (CFA) at Aarhus University has undertaken a study of existing knowledge about the societal impact of Arts and Humanities research. The goal of this study is to review and synthesise work on the impact of A&H research, including how this impact can be conceptualised and the role of funding and evaluation in promoting this research and its impact. The study was funded by the Augustinus Foundation. This study is based on a systematic literature review as well as insights drawn directly from experts in the field of societal impact, A&H researchers and other key stakeholders.